2013
DOI: 10.1051/0004-6361/201220616
|View full text |Cite
|
Sign up to set email alerts
|

Resolving galaxies in time and space

Abstract: Aims. Fossil record methods based on spectral synthesis techniques have matured during the past decade, and their application to integrated galaxy spectra has fostered substantial advances in the understanding of galaxies and their evolution. Yet, because of the lack of spatial resolution, these studies are limited to a global view, providing no information about the internal physics of galaxies. Methods. Motivated by the CALIFA survey, which is gathering integral field spectroscopy (IFS) over the full optical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
224
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 218 publications
(227 citation statements)
references
References 36 publications
1
224
0
Order By: Relevance
“…FIT3D is now part of a more complete spectroscopic analysis pipeline named Pipe3D ), developed to characterise the properties of both the stellar populations and the ionised gas. In the modelling of the continuum emission, FIT3D uses an SSP template grid combining the GRANADA models from González Delgado et al (2005) for t < 63 Myr with those provided by the MILES project (Sánchez-Blázquez et al 2006;Vazdekis et al 2010;Falcón-Barroso et al 2011) for older ages (following Cid Fernandes et al 2013). This grid comprises a total of 156 individual populations covering 39 stellar ages between 0.001 and 14.1 Gyr and four metallicities between 0.004 and 0.03.…”
Section: Measurement Of the Emission Linesmentioning
confidence: 99%
“…FIT3D is now part of a more complete spectroscopic analysis pipeline named Pipe3D ), developed to characterise the properties of both the stellar populations and the ionised gas. In the modelling of the continuum emission, FIT3D uses an SSP template grid combining the GRANADA models from González Delgado et al (2005) for t < 63 Myr with those provided by the MILES project (Sánchez-Blázquez et al 2006;Vazdekis et al 2010;Falcón-Barroso et al 2011) for older ages (following Cid Fernandes et al 2013). This grid comprises a total of 156 individual populations covering 39 stellar ages between 0.001 and 14.1 Gyr and four metallicities between 0.004 and 0.03.…”
Section: Measurement Of the Emission Linesmentioning
confidence: 99%
“…A stellar population fit of the coadded spectra within each spatial bin is then computed. The stellar population model for spaxels with continuum S/N > 3 is then estimated by rescaling the best fitted model within each spatial bin to the continuum flux intensity in the corresponding spaxel, following Cid Fernandes et al (2013) and Sánchez et al (2016a). The stellar mass surface density ( * S ) is then obtained using the stellar mass derived for each spaxel and then normalized to the physical area of one spaxel.…”
Section: Manga Targetsmentioning
confidence: 99%
“…Our method to extract stellar population properties from datacubes has been explained and applied to CALIFA in Pérez et al (2013), Cid Fernandes et al (2013, and González Delgado et al (2014c,a). In short, we analyze the data with the  code (Cid Fernandes et al 2005), which fits an observed spectrum (O λ ) in terms of a model (M λ ) built by a nonparametric linear combination of N simple stellar populations (SSP) from a base spanning different ages (t) and metallicities (Z).…”
Section: Stellar Population Analysis: Differences With Respect To Prementioning
confidence: 99%
“…(9) of Cid Fernandes et al 2013), where x tZ is the fraction of flux at the normalization wavelength (5635 Å) attributed to the base element with age t and metallicity Z. The mass-weighted version of this index, log age M , is obtained by replacing x tZ by its corresponding mass fraction m tZ .…”
Section: Mean Stellar Metallicitymentioning
confidence: 99%